2008
DOI: 10.1093/toxsci/kfn078
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene Disrupts Cardiac Gene Expression and Calcium Homeostasis in Rat Myocytes

Abstract: We have been investigating the molecular mechanisms by which trichloroethylene (TCE) might induce cardiac malformations in the embryonic heart. Previous results indicated that TCE disrupted expression of genes encoding proteins involved in regulation of intracellular Ca2+, [Ca2+](i), in cardiac cells, including ryanodine receptor isoform 2 (Ryr2), and sarcoendoplasmatic reticulum Ca2+ ATPase, Serca2a. These observations are important in light of the notion that altered cardiac contractility can produce morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 44 publications
11
29
1
Order By: Relevance
“…These effects were prevented by methionine, indicating that methyl group availability for DNA methylation was an important factor in mediating the carcinogenicity of TCE in mouse liver. Previously, findings by our laboratory suggested that maternal supplementation with folic acid exacerbated the effects of TCE exposure on the expression levels of genes involved in calcium regulation pathways in both mouse embryonic hearts and rat cardiomyocytes [9]. These cumulative data support the notion that TCE may alter target gene expression by affecting DNA methylation.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…These effects were prevented by methionine, indicating that methyl group availability for DNA methylation was an important factor in mediating the carcinogenicity of TCE in mouse liver. Previously, findings by our laboratory suggested that maternal supplementation with folic acid exacerbated the effects of TCE exposure on the expression levels of genes involved in calcium regulation pathways in both mouse embryonic hearts and rat cardiomyocytes [9]. These cumulative data support the notion that TCE may alter target gene expression by affecting DNA methylation.…”
Section: Introductionsupporting
confidence: 64%
“…Exposure to TCE has also been associated with increased incidence of congenital heart malformations [4,18,39], although past studies have reported inconsistent results [1,4,15], mainly due to differences in experimental conditions. However, recent data from our and other groups [9,13,14,30,33] have supported the notion that exposure to low, environmentally significant doses of TCE affects physiological heart development in both rodent and chick models. In particular, studies using in vitro and in vivo systems [8,9,34] documented that TCE impaired calcium handling in cardiomyocytes, which is controlled largely by the calcium ATPase, Serca2a.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…higher stability, obtained for GAPDH come from the nature of the algorithms followed by both programs. GeNORM and NormFinder consider instability when the pattern of the variation of the gene differs from other [14] 18s rRNA GGGAGGTAGTGACGAAAAATAACAAT TTGCCCTCCAATGGATCCT [15] Fig. 1 Average fold changes ±SD (n = 3) in GAPDH, b-actin and 18s rRNA in AA rats in different organs; *p \ 0.05 vs. baseline expression (dotted line).…”
Section: Discussionmentioning
confidence: 99%